Determination of the Critical Time of Fire in the Building and Ensure Successful Evacuation of People - Hulida, Eduard; Pasnak, Ivan; Koval, Oleksandr; Tryhuba, Anatolii (Periodica Polytechnica Civil Engineering, 2019)
An engineering method was developed for determining the critical time of fire and determining the probability of evacuation of people from zone of fire, which makes it possible, with simplified dependencies, to quickly determine all the necessary factors in the evacuation process of people in case of fire in the building. To explain the use of the developed method, the sequence and example of determining the critical time of fire and determining the probability of evacuation of people from zone of fire for enterprise is considered. It was shown how one could calculate the time of evacuation of people from the premises from the zone of fire. The safety of people is provided when the time of evacuation does not exceed the time of the onset of the critical phase of the development of fire. For this purpose, the period for which the temperature, smoke density, oxygen concentration, hydrogen chloride, carbon dioxide and carbon monoxide gas reaches extremely dangerous values for a person was calculated. After determining all the necessary quantities, the probability of evacuation of people was analyzed in the absence of firefighting equipment in the building. The parameters determined by this new method are adequate and confirmed by other methods of calculation, in particular, developed by Hulida, Koval and FDS program. The relative error between the specified parameters does not exceed 8...12% (in comparison with other mentioned methods).